2012
DOI: 10.1021/la303158c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Study of the Interaction of Cationic Biocides with Lipid Bilayers: Aggregation Effects and Bilayer Damage

Abstract: A novel class of phenylene ethynylene polyelectrolyte oligomers (OPEs) has been found to be effective biocidal agents against a variety of pathogens. The mechanism of attack is not yet fully understood. Recent studies have shown that OPEs cause catastrophic damage to large unilamellar vesicles. This study uses classical molecular dynamics (MD) simulations to understand how OPEs interact with model lipid bilayers. All-atom molecular dynamics simulations show that aggregates of OPEs inserted into the membrane ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 29 publications
(41 reference statements)
3
76
2
Order By: Relevance
“…32 Recent all-atom molecular dynamics simulations on the micro-second timescale reveal that OPE-3 can cause membrane damage that results in water leakage, which may be the initial step that subsequently lead to membrane failure. 38 Our multi-scale characterization of the dark membrane perturbation activity of the CPEs and OPEs using model E. coli plasma membranes so far support a carpet or detergent-like mechanism 9, 24 by which these antimicrobial compounds induce membrane collapse and phase transitions.…”
Section: Resultsmentioning
confidence: 64%
“…32 Recent all-atom molecular dynamics simulations on the micro-second timescale reveal that OPE-3 can cause membrane damage that results in water leakage, which may be the initial step that subsequently lead to membrane failure. 38 Our multi-scale characterization of the dark membrane perturbation activity of the CPEs and OPEs using model E. coli plasma membranes so far support a carpet or detergent-like mechanism 9, 24 by which these antimicrobial compounds induce membrane collapse and phase transitions.…”
Section: Resultsmentioning
confidence: 64%
“…Hill et al performed atomistic MD simulations of polyelectrolyte oligomers and a model bacterial membrane consisting of both zwitterionic (DOPE) and negatively charged (DOPG) phospholipids [93]. Simulations showed that individual cationic oligomers can bind the lipid bilayer surface, driven by the electrostatic interactions with the lipid phosphate groups.…”
Section: Linear Polyelectrolitesmentioning
confidence: 99%
“…Polyphilic molecules are compounds that consist of fragments of different philicity. The molecules used here feature many possibilities of functionalization to tailor the interactions with the membranes toward different goals.…”
Section: Introductionmentioning
confidence: 99%